Analisis kesalahan tatabahasa dalam akhbar Harian Metro dan Metro Ahad - Zakiah, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2017)
Positive advances in information technology led to the development of the print Malay language newspaper that aimed at imparting knowledge, ideas and current information. Accordingly, this study were aimed to identify the Malay language grammatical errors of Metro Harian and Harian Metro newspaper. This study were conducted using the method of content analysis. Results shows that in this newspaper there were grammatical errors in the use of inflection, word classes and phrases. Due to the case, the authors of the newspaper were suggested to take the initiative in producing better quality of writing in compliance with the aspects of grammar. This is in line with honouring Malay language as the national language of Malaysia.